Determination of optical fiber varieties and early diagnosis of their physical condition based on the analysis of Mandelstam–Brillouin backscatter parameters - I. V. Bogachkov (Омский научный вестник)
Research results into the automating the processing of measurement data obtained from the Brillouin optical reflectometer, light guides containing various types of optical fibers are presented in this paper. By analyzing the parameters of the Mandelstam — Brillouin scatter obtained from Brillouin reflectograms, we can classify optical fibers in the studied telecommunication optical cables. This makes it possible to evaluate the change of the Brillouin frequency shift and determine the longitudinal fiber tension. The initial values of the Brillouin frequency shift and the profile of the Mandelstam — Brillouin scatter spectrum are different for each fiber type. The programs for automated processing of Brillouin reflectogram data are discussed. Estimation of the level of the back-reflected signal allows you to identify the factor, that had a predominant effect on the parameters of the Mandelstam — Brillouin scatter signal in the studied sections of optical fibers, and to compensate for the influence of temperature changes in the longitudinal strain distribution graphs. After that, we can plot a graph of the distribution of longitudinal strain along the fiber, caused precisely by mechanical influences on optical fibers. Conclusions about the accuracy of the estimates obtained by various algorithms, based on the accumulated experience in working with the presented programs are drawn.